ACADEMIC LEADERSHIP OF SCHOOL ADMINISTRATORS AFFECTING TEACHER PERFORMANCE UNDER THE OFFICE OF NAKHON SI THAMMARAT PRIMARY EDUCATION AREA 3 - Umpukanon, Kittimon; Somkhaoyai, Teeraphong; Weeraponkan, Boonlert (Journal of MCU Nakhondhat, 2023)
The objectives of this research were to: 1) study the academic leadership of school administrators and teacher performance efficiency; 2) study the academic leadership of school administrators affecting teacher performance; 3) study of guidelines for the development of academic leadership of school administrators that affect teacher performance. This research used mixed method research. Collect data by questionnaire. from a sample of 306 people, statistics used in data analysis were frequency, percentage Mean, standard deviation, and multiple regression analysis. Interviews with 5 key informants and data analysis of qualitative data by descriptive method the results showed that 1) Academic leadership of school administrators overall, it was at a high level and efficiency in teacher performance overall, it was at the highest level. 2) Academic leadership of school administrators affecting the performance of teachers, it was found that educational supervision teacher professional development and promotion and the promotion and development of the teaching profession affect the performance of teachers It was statistically significant at the 0.05 level. 3) Guidelines for the development of academic leadership of school administrators that affect teachers' performance efficiency revealed that administrators had to analyze the school context. Then set a vision and goals together to create the curriculum of the school as well as making a supervision calendar, provide educational supervision by emphasizing on being a coach or mentor, as well as encouraging teachers to do academic work, join the training, continuous seminars and work development with professional standards which is the factor affect performance perform teacher's work effectively.